(untitled) (Carte Romanze, 2023)
Two Middle French versions of the Vie de saint Magloire (a 6th-c. Breton saint) have come down to us, one in prose, still unpublished (ms BnF, fr. 13508, dated 1315), one in verse (ms Arsenal 5122 Réserve, dated 1319, and published in 1957-1959), most probably both derived from the same Latin source. Starting from a short passage – a list of snakes encompassed in a prayer –, this article deals with more general issues: the translation practices in the two texts, the treatment of enumerations, and the relationship between the two versions. Other questions remain open, which only the edition of the prose version may address and solve.